EPIDIDYMAL SPERMATOZOA QUALITY OF ETAWA CROSSBREED GOAT IN TRIS EXTENDER SUPPLEMENTED WITH VARIOUS LACTOSE CONCENTRATIONS - Muhammad Riyadhi; Agus Setiawan; Herdis Herdis; Muhammad Rizal (Jurnal Kedokteran Hewan, 2017)
This research was conducted to investigate the effect of various concentrations of lactose supplementation in Tris extender for maintaining the quality of Etawa crossbreed goat epididymal spermatozoa stored at 3-5° C. Semen in the control group was diluted with a tris extender containing 20% egg yolk without lactose. Semen in the test groups was diluted with a tris extender containing 20% egg yolk and added with 0.3% (0.3 g per 100 mL extender) and 0.6% lactose for group TL1 and TL2, respectively. Parameters evaluated of the fresh epididymal spermatozoa were motility, concentration, percentage of live, and abnormality of spermatozoa, while for diluted-spermatozoa were motility and percentage of live spermatozoa. Spermatozoa observation was conducted until it reaches 40% motility. The results showed that the mean percentage of motility, live sperm, concentration, and abnormality of epididymal spermatozoa were 70%; 81%; 3,220x106 cells/mL; and 4.30%, respectively in all group. After dilution, the percentage of motility and live spermatozoa were also 70% and 81.00±1.58%, respectively in all groups. The decreasing of spermatozoa motility was observed on day 4 of storage, in which percentage of spermatozoa motility in control group (40.00±0.00%) was significantly lower (P0.05) than those in TL1 (44.00±2.24%) and TL2(45.00±0.00%) groups. Percentage of live spermatozoa in control (63.20±2.68%) was not significantly different (P0.05) than TL1(65.40±1.95%) and TL2 (65.60±1.95%). In conclusion, the supplementation of lactose into Tris extender could maintain the epididymal spermatozoa of Etawa crossbreed for 3 days of storage at 3-5° C.